2019
DOI: 10.1186/s40462-019-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

The start of migration correlates with arrival timing, and the total speed of migration increases with migration distance in migratory songbirds: a cross-continental analysis

Abstract: Background Anthropogenic changes in the climate and environment have globally affected ecological processes such that the spatiotemporal occurrence of the main annual cycle events (i.e., breeding, wintering, moulting, and migration) has shifted in migratory birds. Variation in arrival timing at migratory destinations can be proximately caused by an altered start of migration, total migration distance, and/or total speed of migration. Quantifying the relative contributions of these causes is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 130 publications
7
32
4
Order By: Relevance
“…Our results of activity and barometric pressure tracking revealed that tawny pipits predominantly migrate at night contradicting the earlier notion of the species as a typical diurnal migrant (Dorka , Alerstam , Schmaljohann ). We found that landing most often occurred within the first four hours after sunrise, which could explain the earlier observation‐based assumption of diurnal migration by tawny pipits.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results of activity and barometric pressure tracking revealed that tawny pipits predominantly migrate at night contradicting the earlier notion of the species as a typical diurnal migrant (Dorka , Alerstam , Schmaljohann ). We found that landing most often occurred within the first four hours after sunrise, which could explain the earlier observation‐based assumption of diurnal migration by tawny pipits.…”
Section: Discussioncontrasting
confidence: 99%
“…Here we use multi‐sensor individual tracking to describe migratory patterns and flight behaviour over the entire journey of tawny pipits Anthus campestris breeding in Central Europe. The tawny pipit is among the few Afro‐Palearctic migratory species that are characterized as a ‘typical diurnal migrant’ (Dorka , Alerstam , Schmaljohann ), however, conclusive evidence is still missing. We employ novel analytical tools to test this long‐standing assumption with a particular focus on describing flight and stopover behaviour and take‐off and landing times of pipits in relation to sunset/sunrise throughout the migration journey.…”
Section: Introductionmentioning
confidence: 99%
“…Conforming to the predicted effect of travel distance on travel speed, we found that longer-distance migratory songbirds have faster migration speeds. Similar findings were also reported in a recent analysis of migration speed among and within species of songbirds that used some of the same sources of data as ours, but used a different statistical approach (Schmaljohann, 2019). While these results are encouraging, estimated migration speed does not include the fueling episode before the first migratory flight.…”
Section: Traitsupporting
confidence: 88%
“…Increases in global average temperatures have been welldocumented in the literature, but other characteristics of temperature, like regional and seasonal variability or timing, have been less well studied (Allen and Sheridan 2016;Rogers 2013;Trenberth 1983). Among the different thermal characteristics of climate change, timing is an important issue for many bio-climatological processes, as, e.g., earlier onset of spring/summer or delayed onset of autumn and shortening of winter can have impacts on flowering dates (Sperling et al 2019;Woznicki et al 2019), migratory species (Fraser et al 2019;Helm et al 2019;Schmaljohann 2019), and human adaptation to extreme temperature environments. In this work, we developed a new configuration of the seasons in order to quantify changes in timing in thermal climate characteristics.…”
Section: Discussionmentioning
confidence: 99%